Life on the Orinoco - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
The Orinoco River is one of the longest rivers in the world. Many lives depend on this river. Many people, animals and plants live in or near the water
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography